A tough scope to swallow: endoscopic retrograde cholangiopancreatography through percutaneous endoscopic gastrostomy - Amjad, Waseem; Hussain, Qulsoom; Ullah, Waqas; Hurairah, Abu (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Amjad W, Hussain Q, Ullah W, Hurairah A. A tough scope to swallow: endoscopic retrograde cholangiopancreatography through percutaneous endoscopic gastrostomy. Turk J Gastroenterol 2018; 29: 119-21